Pengembangan “Flip Digital Learning” sebagai Inovasi Media Pembelajaran Cerita Hikayat untuk Siswa Kelas X SMA/MA (SATU Press Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2022)
The purpose of this research and development is to produce a learning media Flip Digital Learning as a medium for learning storytelling for 10th grade SMA/MA students. This is an innovative step to support online learning which has been experiencing obstacles. With this media, students are expected to have enthusiasm during learning activities. Based on the due diligence conducted by experts and teachers, the media feasibility percentage was obtained by 97% from experts and 93% from teachers. While the results of limited trials conducted on students obtained results of 89%. This data can be believed that this media is very good so that it can support the achievement of learning objectives.